Adult Stem Cells Exhibit Global Suppression of RNA Polymerase II Serine‐2 Phosphorylation - Freter, Rasmus; Osawa, Masatake; Nishikawa, Shin‐Ichi (Stem cells (Dayton, Ohio), 2010)
Adult stem cells, which are characterized by their capacity for self‐renewal and differentiation, participate in tissue homeostasis and response to injury. They are thought to enter a state of relative quiescence, known as reversible cell cycle arrest, but the underlying molecular mechanisms remain poorly characterized. Previous data from our laboratory has shown that housekeeping gene expression is downregulated in melanocyte stem cells (MelSCs), suggesting a global suppression of mRNA transcription. We now show, using antibodies against specific phosphorylated forms of RNA polymerase II (RNApII), that adult MelSCs do not undergo productive mRNA transcription elongation, while RNApII is activated and initialized, ready to synthesize mRNA upon stimulation, and that the RNApII kinase CDK9 is absent in adult MelSCs. Interestingly, other adult stem cells also, including keratinocyte, muscle, spermatogonia, and hematopoietic stem cells, showed a similar absence of RNApII phosphorylation. Although it is difficult to show the functional significance of this observation in vivo, CDK9 inhibition resulted in enhanced survival of cells that are deprived from survival factors. We conclude that the absence of productive mRNA transcription is an early, specific, and conserved characteristic of adult stem cells. Downregulation of mRNA transcription may lead to decreased rates of metabolism, and protection from cellular and genetic damage. Screening heterogeneous tissues, including tumors, for transcriptionally quiescent cells may result in the identification of cells with stem cell‐like phenotypes. STEM CELLS 2010; 28:1571–1580.